1991
DOI: 10.1002/1097-0142(19910301)67:5<1359::aid-cncr2820670515>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Lymphomas of the breast. A clinicopathologic and immunohistochemical study of primary and secondary cases

Abstract: Primary mammary lymphoma is rare, and little is known about the immunophenotype of such cases. The authors studied both primary and secondary breast lymphomas with a broad panel of T‐ and B‐cell markers using paraffinembedded tissue and the avidin–biotin immunoperoxidase method. Cases of primary B‐cell lymphoma were further tested to determine light and heavy chain type. Thirty‐five cases were analyzed, including 16 primary lymphomas. Diffuse large cell lymphoma was present in ten of 16 primary and 14 of 18 se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
90
2

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(105 citation statements)
references
References 46 publications
13
90
2
Order By: Relevance
“…The initial features of the 38 high-grade NHL patients included in our study were compared with reported data in Table III [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. In our series and in these reports, almost all cases had a B-cell non-Hodgkin's lymphoma, which was high-grade in about 80% of cases (range: 50-100%), and particularly of DLBCLs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The initial features of the 38 high-grade NHL patients included in our study were compared with reported data in Table III [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. In our series and in these reports, almost all cases had a B-cell non-Hodgkin's lymphoma, which was high-grade in about 80% of cases (range: 50-100%), and particularly of DLBCLs.…”
Section: Discussionmentioning
confidence: 99%
“…First described in 1959 [1], primary breast lymphoma (PBL) is a rare site of this disease, representing less than 1% of all NHL [2][3][4][5][6] and about 2% of extra-nodal presentations [2,4,5,[7][8][9]. In the same way, NHL are rare malignant tumors of the breast, representing less than 1% of all breast cancers [2,3,[5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peripheral T-cell lymphomas compose less than 15% of all non-Hodgkin's lymphomas (51) and are extremely rare in the breast, representing 0.04 to 0.5% of all breast malignancies (1)(2)(3)(4)(5). T-cell lymphomas, particularly nodal peripheral T-cell lymphomas, have an aggressive course and usually present with generalized disease, although some subtypes may be less malevolent in behavior (51).…”
Section: Discussionmentioning
confidence: 99%
“…Non-Hodgkin's lymphoma (NHL) of the breast is uncommon, composing 0.04 to 0.5% of all malignant breast tumors (1)(2)(3)(4)(5). Most primary breast lymphomas are of B-cell phenotype or have not been immunophenotyped; only rare cases have been reported as T-cell in series of lymphomas of the breast .…”
mentioning
confidence: 99%